Pro-export policy of the Czech Republic (with focus on activities of CzechTrade and CzechInvest) - Koschantová, Klára (2013)
My bachelor thesis deals with the pro-export policy of the Czech Republic. The first part is devoted to export promotion policies and institutions through which this support is implemented. In the second part, I took a closer look primarily at two of these institutions, namely CzechTrade and CzechInvest, whose work I will try to analyze and evaluate. Based on this work, I would like to verify whether the current market support is sufficient, and to evaluate whether this support is implemented correctly and effectively. In conclusion I also mention the planned merger of these agencies.